Probit Regression Analysis in Estimating the Effect of Learning Assisted by Cabri 3D on Students' Mathematical Understanding Ability - Marlena, Leni; Nugraheni, Esti Ambar (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
Social connection requires each individual to have a strong understanding of the environment. Concept understanding can be improved through software. The goal of this research is to predict the effect of mathematics learning using Cabri 3D software. The dependent variable is the mathematics concept of understanding ability. The independent variable is the dummy variable that determines the type of the class. The value of the dummy variable for the class that applied the Problem-based Learning (PBL) assisted by Cabri 3D is 1 and the value of the dummy variable for class without Cabri 3D is 0.  Students' mathematics ability was measured by a percentage or probability. The values of the mathematical concept understanding obtained by students were converted into probability values. After the data has been collected, probit regression analysis was used to see the probability of success of mathematical concepts understanding of those who were taught using PBL and those who were taught without using PBL without Cabri 3D. The results of data analysis showed that the types of classes significantly affect the mathematical concept of understanding ability. Thus, it can be concluded that learning with Cabri 3D can improve the mathematical concept of understanding ability.